Roselle powder proportion in the aging process enhances pidan’s antioxidant activity and hedonic value - Susanti, Siti; Rizqiati, Heni; Nuryanto, Nuryanto; Purwitasari, Lutfi; Arifan, Fahmi (Journal of Advanced Veterinary Research, 2025)
This study was about the potential of roselle (Hibiscus sabdariffa Linn.) powder as a functional compound in the production of pidan eggs. The research was evaluating its antioxidant activity, chemical composition, and sensory characteristics. In this study, roselle powder was used to partially replace the red brick which traditionally included in the coating mixture, at substitution levels of 0%, 10%, 20%, 30%, 40%, and 50%, while keeping the amount of black tea constant. Antioxidant activity was determined using the DPPH radical scavenging assay, chemical composition was assessed using AOAC methods, and sensory evaluation was conducted by trained panelists using a hedonic scale. The results showed that increasing roselle concentration significantly enhanced antioxidant activity, with the highest activity recorded at the 50% substitution level (91.60 ppm). The fat and protein content remained relatively stable across treatments, ranging from 21% to 24% for fat and 16% to 18% for protein. Sensory evaluation indicated that higher Roselle levels improved color, excessive concentration negatively affected aroma and taste, and the best overall acceptability achieved at the 20% substitution level. The addition of roselle powder to production of pidan eggs effectively enhanced the antioxidant properties without substantially affecting their nutritional profiles. The best acceptability of the pidan was achieved with a 20% addition of roselle.